Characterization of water absorption, mechanical and thermal properties of recycled cellulose fibre reinforced vinyl-ester eco-nanocomposites - Alhuthali, Abdullah; Low, It Meng; Dong, Chensong (Elsevier, 2012)
Natural fibres are cheaper and have a lower density compared to synthetic reinforcement products and therefore offer benefits for use in commercial applications. The physical and mechanical properties of these ‘eco-composites’ can be further enhanced through the addition of nanoclay. This paper reports on the fabrication of vinyl ester, eco-composites and eco-nanocomposites and characterises these samples in terms of water absorption, strength, toughness, and thermal properties. Weight gain and FTIR spectrum analysis indicated that 5% nanoclay addition gave favourable reduction in the water absorption behaviours of the samples. Nanoclay addition strengthened fibre–matrix adhesion leading to improved strength properties in the eco-nanocomposites. However, SEM images of fracture surfaces revealed that nanoclay addition limited toughness mechanisms of fibre pull-out and fibre debonding leading to sample brittleness. Eco-nanocomposites were still found to have favourable thermal stability and flammability results.